Survey of antimicrobial susceptibility patterns of the bacteria of the Bacteroides fragilis group isolated from the intestinal tract of children - Viviane Nakano; Mario Julio Avila-Campos (Memorias do Instituto Oswaldo Cruz, 2004)
The bacteria of the Bacteroides fragilis group are considered important clinical pathogens and they are the most common anaerobes isolated from human endogenous infections. In this study, the susceptibility patterns to antibiotics and metals of 114 species of the B. fragilis group isolated from children with and without diarrhea were determined. Susceptibility was assayed by using an agar dilution method with Wilkins-Chalgren agar. All B. fragilis strains were resistant to lead and nickel, but susceptible to metronidazole and imipenem. beta-lactamase production was detected by using biological and nitrocefin methods, respectively, in 50% and 90.6% of the isolates of children with diarrhea and in 60% and 90% of the isolates of children without diarrhea. Our results show an increase of antibiotics and metals resistance in this microbial group, and a periodic evaluation of the antimicrobial susceptibility is needed. In Brazil, the contamination for antibiotics or metal ions is often observed, and it is suggested an increase the antimicrobial resistance surveillance of this microbial group, mainly those isolated from children's diarrhea.